Peramalan Harga Minyak Goreng di Kalimantan Timur Menggunakan Model Hybrid Time Series Regression Quadratic – Neural Network - Wahyuni, Risa Kristia; Wahyuningsih, Sri; Siringoringo, Meiliyani (Program Studi Statistika FMIPA Universitas Mulawarman, 2023)
A hybrid model is a combination of two or more forecasting methods. One of hybrid model that can be used in forecasting is Time Series Regression (TSR) Quadratic – Neural Network (NN). TSR Quadratic can be used in time series data that contains quadratic trend patterns, namely an increase or decrease that forms a curved or parabolic line NN is a method that has characteristics similar to biological neural networks in conducting data pattern recognition. This study was aimed to obtain a hybrid model of TSR quadratic-NN to forecast cooking oil prices in East Kalimantan and obtain forecasting results based on the best model. The results showed that the TSR Quadratic-NN hybrid model with 3 neurons in the hidden layer was the best model with a MAPE of 2.51368%. The forecasting results based on this model showed that cooking oil prices in East Kalimantan from January to December 2023 showed an increase